Delayed Migration of Embolized Coil with Large Renal Stone Formation: A Rare Presentation - Santosh Kumar; Kumar Jayant; Shrawan K. Singh; Kalpesh M. Parmar; Sudheer K. Devana; Gautam R. Choudhari; Ankur Mittal (Case Reports in Urology)
Delayed bleeding following percutaneous nephrolithotomy (PCNL) usually occurs due to development of the pseudoaneurysm which can be successfully managed with coil embolization. However very few cases of such complications have been reported in the literature. Here we are reporting a case of delayed post-PCNL bleeding that occurred in a 53-year-old diabetic patient operated on for renal stone. Computed tomography scan revealed a presence of the pseudoaneurysm in the segmental branch of right renal artery, which was successfully managed with coiling. Patient remained asymptomatic for the next 9 years after which he again presented with similar complaints. X-ray KUB was done which revealed a 2.7 cms renal pelvic calculus with the migrated coil in its center and a left upper ureteric calculus. His routine haemogram, coagulogram, serum electrolytes, and liver function tests, renal function tests, vitamin D3, and PTH (parathyroid hormone) were within normal limits. He underwent left laparoscopic ureterolithotomy and right percutaneous nephrolithotomy (PCNL). Intraoperatively the migrated stainless steel embolization coil was seen engulfed all around by the multiple stones in the right renal pelvis. Postoperative period was uneventful. Later he was followed in the outpatient department and was doing well. To conclude, this is the only case report of development of a large calculus around a migrated embolization coil which was successfully managed with PCNL. PCNL offers better stone clearance in cases of stones being formed over foreign bodies like fragmented double J stents, fragmented nephrostomies, or migrated embolization coil.